Acoustic Emission Reveals Multiple Slip Modes on a Frictional Fault - Ostapchuk, Alexey; Morozova, Kseniya; Markov, Vadim; Pavlov, Dmitry; Popov, Maxim (Frontiers in Earth Science, 2021)
The spectrum of fault slip modes spans a continuum from fast ruptures to slow slip events. The nucleation of a certain slip mode is governed by the frictional heterogeneity of fault interface and the rheological fault stiffness. There is a mounting evidence that a single fault can host multiple slip modes. In laboratory experiments we study acoustic emission (AE) initiated by a sliding frictional fault and focus our attention on gouge-filled faults hosting multiple slip modes. Deformation experiments were performed on a slider model setup with a precise control of mechanical parameters and monitoring the acoustic signal in the frequency range of 20-80 kHz. We have shown that the cumulative AE energy linearly depends on block displacement. Besides that, there is a high inverse correlation (-0.94) between fault friction and b-value of frequency-amplitude distribution of AE in the performed experiments. Provided that velocity weakening is specific for the fault interface, the self-organization of a gouge-filled fault at the micro scale is the key parameter that controls the frictional behavior of fault hosting multiple slip modes. Resting on a quantitative categorization of AE waveforms, two AE subpopulations have been distinguished. One of them manifests as AEs with harsh onsets. The second one exhibits a gradual amplitude rise and tremor-like waveforms. A longer duration of the intergrain rupture is specific for the second AE subpopulation. During a laboratory seismic cycle, the first AE subpopulation retains parameters, while the second one exhibits a pronounced cyclic recurrence of b-value. The b-value of the second subpopulation gradually decreases before slip events and recovers after them. Two AE subpopulations, probably, point to the coexistence of two dynamic subsystems. The revealed precursory changes of AE subpopulations are common for the entire spectrum of slip modes. We speculate on the unity of underlying mechanisms of different slip modes.